2013
DOI: 10.1364/ol.38.004425
|View full text |Cite
|
Sign up to set email alerts
|

Efficient dual-wavelength Nd:LuLiF_4 laser

Abstract: We report an efficient continuous-wave (CW) and passively Q-switched dual-wavelength Nd:LuLiF 4 laser at 1314 and 1321 nm for the first time. Maximum CW output power of 6.08 W is obtained, giving an optical-to-optical conversion efficiency of 30.2% and a slope efficiency of 32.1%. Even using high doping V 3 :YAG as the saturable absorber to passively Q-switch the laser, stable dual-wavelength operation remains. Maximum pulse energy extracted from the resonator is 108.7 μJ at 17.2 kHz pulse-repetition rate, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Under the maximum output power, the beam quality parameter M 2 of the CW laser beam was measured to be 1.12 in tangential plane and 1.19 in sagittal plane, respectively, by using a 10.0/90.0 knife-edge method, indicating a nearly diffraction limited output beam and being better than that in Ref. [15]. While the M 2 factor for Q-switched laser beam was measured to be 1.19 in tangential plane and 1.26 in sagittal plane, respectively.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…Under the maximum output power, the beam quality parameter M 2 of the CW laser beam was measured to be 1.12 in tangential plane and 1.19 in sagittal plane, respectively, by using a 10.0/90.0 knife-edge method, indicating a nearly diffraction limited output beam and being better than that in Ref. [15]. While the M 2 factor for Q-switched laser beam was measured to be 1.19 in tangential plane and 1.26 in sagittal plane, respectively.…”
Section: Resultsmentioning
confidence: 80%
“…[18], lower slope efficiency and less output power were obtained than those in Ref. [15]. Then passively Q-switched Nd:LLF laser performance was investigated by inserting the Bi-GaAs into the cavity.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Here, in order to compare the experiment results with those in Ref. [5], these two output coupling transmissions were chosen. Further increasing the pump power, the FWHM of the laser spectrum in each wavelength became broader.…”
Section: Resultsmentioning
confidence: 99%
“…Dual-wavelength Nd:YLF lasers at 1312 and 1322.6 nm have been demonstrated by Louyer et al in 2003 [1]. In 2013, Li et al reported continuous-wave (CW) dual-wavelength Nd:LuLiF 4 (Nd:LLF) laser operation at 1314 and 1321 nm [5]. However, the PQS dual-wavelength Nd:LLF laser at 1.3 μm with V:YAG was only obtained with the 3% output coupling beyond a certain absorbed pump power.…”
mentioning
confidence: 99%